Ectomycorrhizal fungi and the enzymatic liberation of nitrogen from soil organic matter why evolutionary history matters - Pellitier, Peter T (The New phytologist, 2018)
© 2017 The Authors. New Phytologist © 2017 New Phytologist Trust.